Psychosocial Aspects of Healthcare Workers during the Covid-19 Pandemic: A Scoping Review - Buyung Reza Muhammad; Shanti Wardaningsih (Alta Dharma Publisher, 2021)
The transmission of COVID-19 could have physical, psychological and social impacts, especially on healthcare workers. As healthcare workers, nurses were often faced with situations that made their work more difficult and were at risk for infection due to the transmission of COVID-19. This scoping review used a 5-stage methodology developed by Arksey and O'Malley which aimed to identify psychosocial impacts on healthcare workers. This review used 4 databases (PubMed, Springer, Sagejournals, Science Direct) which were limited to 2019-2021. The total study obtained 731 articles, meanwhile, only 7 articles met the criteria. The study's inclusion criteria were in full-text form, population of healthcare workers, English and original articles. From the 7 articles obtained, it was mentioned several psychological and social disorders among healthcare workers, including major depressive disorder, generalized anxiety disorder, panic, post traumatic stress disorder and substance use disorder. Anxiety, depression, somatization, moderate-high levels of anxiety, depression, fear, acute stress disorder and coping, self-efficacy, insomnia, being the target of community rejection, discrimination, and stigmatization could affect health services. Therefore, healthcare workers as the front line who faced the risk of psychological and social disorders directly, needed special attention that could affect the quality of health services.